Attachment patterns and autobiographical episodic memory functioning: A systemic review of adult studies to advance clinical psychological science. (April 2023) - Lau-Zhu, A.; Williams, F.; Steel, C.
Abstract: Patterns of insecure attachment are associated with psychopathology but the mechanisms involved remain poorly understood. Cognitive science proposes that attachment patterns are influenced by the autobiographical memory system and in turn influence its ongoing functioning. Disturbances in autobiographical memory represent cognitive risks for later emotional difficulties. We systemically reviewed 33 studies (in 28 articles) examining the association between attachment patterns and autobiographical episodic memory (AEM) in individuals from the age of 16 (i.e., from young to older adulthood). Attachment patterns were associated with key areas of AEM phenomenology, including intensity and arousal; detail, specificity, and vividness; coherence and fragmentation; and accuracy and latency. These associations appeared to be moderated by contextual and individual factors; mediated by emotional regulation and schema-based processing; linked to mental health outcomes. Attachment patterns may also influence the impact of certain AEM-based manipulations. We conclude by providing a critical discussion and a research agenda for bringing together attachment, memory, and emotion, with a view to promote mechanism-driven treatment innovation in clinical psychology. Highlights: Insecure attachment is associated with a distinct pattern of autobiographical memory recall. Memories can be less intense, detailed, coherent and slower in avoidantly-attached adults. Memories can be more intense and faster (and less detailed) in anxiously-attached adults but with more mixed data. Memory therapeutics should consider individual differences in attachment patterns.